PROFILE OF SMALL INTERFERING RNAS FROM FRENCH BEAN PHASEOLUS VULGARIS UNDER ABIOTIC STRESS CONDITIONS - NAGESHBABU R; JYOTHI M.N (International Journal of Pharma and Bio Sciences, 2013)
Drought and salinity stresses significantly altered microRNA (miRNA) expression in a dose-dependent manner in French bean seedlings. Salinity stress changed the miRNA expression levels from a 6.86-fold down-regulation to a 616.57-fold up-regulation. Alternatively, miRNAs were down-regulated by 2.68-fold and up-regulated 2810-fold under drought conditions. miR395 was most sensitive to both stresses and was up-regulated by 616 and 2810-folds by 1.00% PEG and 0.4 M NaCl, respectively. Salinity and drought stresses also changed the expression of protein-coding genes [alcohol dehydrogenase (ADH) and ascorbate peroxidase (APX)]. The results suggest that miRNAs may play an important role in plant response to environmental abiotic stresses. Further investigation of miRNA-mediated gene regulation may elucidate the molecular mechanism of plant tolerance to abiotic stresses and has the potential to create a miRNA-based biotechnology for improving plant tolerance to drought and salinity stresses.